1851-1852 Ga. Laws 269, no. 165 - (:unkn) unknown (General Publisher, 1852)
Prohibited the concealed carry of any pistol, dirk, sword in a cane, spear, Bowie knife, or any other kind of knives manufactured and sold for the purpose of offense or defense.
--
Keywords: CARRY - CONCEALED